Recent Results from the MAXIMA Experiment - Jaffe, A; Abroe, M; Borrill, J; Collins, J; Ferreira, P; Hanany, S; Johnson, B; Lee, A; Matsumura, T; Rabii, B; Renbarger, T; Richards, P; et al. (2003)
MAXIMA is a balloon-borne platform for measuring the anisotropy of the Cosmic Microwave Background (CMB). It has measured the CMB power spectrum with a ten-arcminute FWHM beam, corresponding to a detection of the power spectrum out to spherical harmonic multipole l~1000. The spectrum is consistent with a flat Universe with a nearly scale-invariant initial spectrum of adiabatic density fluctuations. Moreover, the MAXIMA data are free from any notable non-Gaussian contamination and from foreground dust emission. In the same region, the WMAP experiment observes the same structure as that observed by MAXIMA, as evinced by analysis of both maps and power spectra. The next step in the evolution of the MAXIMA program is MAXIPOL, which will observe the polarization of the CMB with comparable resolution and high sensitivity over a small patch of the sky.